STRATEGI SMP LABSCHOOL UNESA 1 SURABAYA DALAM MENGHADAPI PERUBAHAN KEBIJAKAN PPDB - Rahma Maulida (Seminar Nasional Ilmu Terapan, 2024)
The existence of a zoning system in Public Junior High Schools gets impact in Private Junior High Schools especially in a decrease in the number of new student admissions. Likewise, Junior High School of Labschool Unesa 1 Surabaya has experienced a decrease in the number of students, but in recent years the school has experienced an increase in the number of students although the number is not comparable to the previous decrease. The researcher intends to analyze the school's strategy by formulating the problem, Namely "What is the Form and Implementation of the school's strategy in an effort to increase the acceptance of new students? Then what is the impact of the implementation of the school's strategy on efforts to increase the acceptance of new students?". The purpose of this study is to determine the effectiveness of the form and implementation of the school's strategy, as well as the impact which occurs after implementing the school strategy that has been made. This study uses a qualitative research method, so that researcher can explore the meaning of the visible inequality phenomenon and obtain concrete, detailed, and transparent data. The informants in this study are one principal, one school staff teacher, three guardians and five students, all of them are informants. The data is obtained from the interview, then it is processed through the stages of data collection, data reduction, data presentation, and drawing conclusions. The result of this study is that Junior High School of Labschool Unesa 1 Surabaya uses two strategies, namely promotion strategy and school branding strategy, these strategies turn out to be effective for the sustainability of the PPDB process. The impact felt is that the school experiences an increase in the number of students, although the increase is not comparable to the decrease that is occurred and the school become better and it is known by the community.